2018
DOI: 10.1016/j.jacc.2018.03.534
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis in Patients With Bicuspid Aortic Valve or Mitral Valve Prolapse

Abstract: IE in patients with BAV and MVP have higher rates of viridans group streptococci IE and IE from suspected odontologic origin than in other IE patients, with a clinical profile similar to that of high-risk IE patients. Our findings suggest that BAV and MVP should be classified as high-risk IE conditions and the case for IEAP should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 39 publications
1
40
0
2
Order By: Relevance
“…In 2007, the American Heart Association (AHA) removed two prior cardiac conditions for endocarditis prophylaxis [8]. Patients with mitral valve prolapse and bicuspid aortic valve (BAV) are now restricted from prophylactic antibiotic use; however, recent data show Case Reports in Infectious Diseases an increased incidence of infective endocarditis within this population with an increased risk of perivalvular extension with abscess formation [9,10]. Based on congenital valvular literature, BAV is the most common congenital heart disease with estimated prevalence of around 0.5-2.0% [10].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, the American Heart Association (AHA) removed two prior cardiac conditions for endocarditis prophylaxis [8]. Patients with mitral valve prolapse and bicuspid aortic valve (BAV) are now restricted from prophylactic antibiotic use; however, recent data show Case Reports in Infectious Diseases an increased incidence of infective endocarditis within this population with an increased risk of perivalvular extension with abscess formation [9,10]. Based on congenital valvular literature, BAV is the most common congenital heart disease with estimated prevalence of around 0.5-2.0% [10].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients with pure aortic regurgitation seemed to demonstrate preference for younger age, male gender, and RL fusion type, and were inclined to develop aortic root dilatation. As a potentially devastating complication, infective endocarditis remains a big challenge, 21) especially among young regurgitant BAV patients. The occurrence of endocarditis was 3.2% in the present study, which was in agreement with a recent cross-sectional study by Li et al 22) Similar incidences could be found in follow-up studies by Michelena, et al and Tzemos, et al in 2008, while Roberts reported a much higher occurrence in his pilot BAV autopsy study in 1970.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of BAV with IE were men. Adverse events of IE included heart failure, peripheral embolism, embolic stroke, persistent bacteremia, and intracardiac complications (Chambers, 2018; Zegri-Reiriz et al, 2018).…”
Section: Infective Endocarditis: Antibiotic Prophylaxis Comes Firstmentioning
confidence: 99%